Autonomy or subordination of labour law? - Birgillito, Marialaura (Delavci in delodajalci, 2017)
The article presents the retrospective overview on the debate held in 2015 in 22 out of 28 journals affiliated with the International Association of Labour Law Journals (IALLJ). In their analysis, the authors decided to pay particular attention to the issue of autonomy and/or subordination of labour law from other disciplines and took therefore into account its relationship with international and humanitarian law, constitutional law (intended in a broad sense, i.e. considering the protection of social rights in a multilevel legal order) and economics.
Keywords: avtonomija; delovno pravo; strokovni članki; znanstveni članki